Chronic exposure to insufficient sleep alters processes of pain habituation and sensitization. Issue 1 (January 2018) - Simpson, Norah S.; Scott-Sutherland, Jennifer; Gautam, Shiva; Sethna, Navil; Haack, Monika
Abstract : Abstract: Chronic pain conditions are highly comorbid with insufficient sleep. While the mechanistic relationships between the 2 are not understood, chronic insufficient sleep may be 1 pathway through which central pain-modulatory circuits deteriorate, thereby contributing to chronic pain vulnerability over time. To test this hypothesis, an in-laboratory model of 3 weeks of restricted sleep with limited recovery (5 nights of 4-hour sleep per night followed by 2 nights of 8-hour sleep per night) was compared with 3 weeks of 8-hour sleep per night (control protocol). Seventeen healthy adults participated, with 14 completing both 3-week protocols. Measures of spontaneous pain, heat-pain thresholds, cold-pain tolerance (measuring habituation to cold over several weeks), and temporal summation of pain (examining the slope of pain ratings during cold water immersion) were assessed at multiple points during each protocol. Compared with the control protocol, participants in the sleep-restriction protocol experienced mild increases in spontaneous pain ( P < 0.05). Heat-pain thresholds decreased after the first week of sleep restriction ( P < 0.05) but normalized with longer exposure to sleep restriction. By contrast, chronic exposure to restricted sleep was associated with decreased habituation to, and increased temporal summation in response to cold pain (both P < 0.05), although only in the past 2 weeks of the sleep-restriction protocol. These changes may reflect abnormalities in central pain-modulatory processes. Limited recovery sleep did not completely resolve these alterations in pain-modulatory processes, indicating that more extensive recovery sleep is required. Results suggest that exposure to chronic insufficient sleep may increase vulnerability to chronic pain by altering processes of pain habituation and sensitization. Abstract : Pain-modulatory processes deteriorate with more chronic forms of sleep insufficiency and a couple of nights with limited recovery sleep do not resolve alterations.